Treatment of Petroleum Drill Cuttings Using Stabilization/Solidification Method by Cement and Modified Clay Mixes - Soroush Ghasemi; Saeid Gitipour; Fereydoun Ghazban; Hamed Hedayati (Iranian Journal of Health, Safety and Environment, 2017)
High organic content in petroleum drill cuttings is a substantial obstacle which hinders cement hydration and subsequently decreases the clean-up efficiency of the stabilization/solidification (S/S) process. In this study, a modified clayey soil (montmorillonite with low to moderate polarity) was used as an additive to cement. Because of its high adsorption capacity, the clay is capable of mitigating the destructive role of organic materials and preventing their interference with the hydration process. Mixes containing different ratios of cement, waste and modified clay were prepared and tested for their mechanical and chemical characteristics. Total petroleum hydrocarbons (TPH) and Pb content of the samples were analyzed as well. For this purpose, the mixes were subjected to unconfined compressive strength (UCS) and toxicity characteristic leaching procedure (TCLP) tests. The results indicated that the specimens with 28-day curing time at a cement/waste ratio of 25% or higher (w/w) and 10% modified clay (w/w) met the Environmental Protection Agency (EPA) criterion for compressive strength. Moreover, a reduction of 94% in the leaching of TPH was observed with the specimens undergoing the TCLP with a cement/waste ratio of 30% (w/w) and a clay/waste ratio of 30% (w/w). Finally, the specimens with 30% cement/waste and 10% clay/waste ratios showed the least concentration (6.14%) of leached Pb.